P113 Starting a research collaborative in the midst of a pandemic – the Humberside experience. (8th April 2021) - Totty, J; Hitchman, L; Wilkins, A; Loubani, M; ,; Totty, Joshua
Abstract: Introduction: The COVID-19 pandemic severely impacted research activities. Large international research collaboratives have successfully produced high quality COVID-related research. We aimed to investigate factors that influence trainee engagement in collaborative research and quantify engagement in our local area to propose methods to ensure all trainees have the opportunity to take part in impactful research. Methods: This is a mixed methods study consisting of a survey to trainees regarding their experiences in research and an assessment of engagement in COVID-related research. The survey was circulated to undergraduates and trainees of all grades in February 2020. Results: Engagement with the survey was poor, with a < 10% return rate. 43% of respondents stated that they had no experience of research. Engagement with collaborative research was popular, with responders declaring involvement with at least 7 other collaboratives. Reasons for participating in research were improving patient care (23%), producing high quality research (19%) and CV building (19%). Barriers included perceived lack of time (23%) and lack of knowledge about research (23%). The CASSH collaborative co-ordinated the local response to COVIDSurg, COVIDSurg|Cancer and the COVER study, involving 20 trainees contributing data on 368 patients. Conclusions: All research collaboratives rely on the enthusiasm of participants in order to succeed. We have presented some of the motivators and barriers to participation in our region and outlined how we have built on national projects to improve engagement on a local level. Further projects are planned to capitalise on this improved engagement.